THE INFLUENCE OF THE 7P MARKETING MIX ON OUTPATIENTS’ REVISIT INTENTION (A SURVEY STUDY AT DR. AGUNG HOSPITAL, BIMA CITY) - ST. Hajar; Sri Rochani Mulyani; Etty Sofia Marianti Asnar (RADJA PUBLIKA, 2026)
In the increasingly competitive healthcare sector, hospitals are required not only to provide high-quality medical services but also to implement effective marketing strategies. This study aims to analyze the influence of the 7P marketing mix (product, price, place, promotion, people, process, and physical evidence) on outpatients’ revisit intention at dr. Agung Hospital, Bima City. A quantitative approach with a descriptive-verificative method was employed. The study involved 195 outpatients selected through purposive sampling. Data were collected using questionnaires and analyzed with multiple linear regression. The results show that the 7P marketing mix variables simultaneously have a significant effect on revisit intention, with a model contribution of 68.8% (R² = 0.688). Partially, price (p = 0.004), people (p = 0.000), and physical evidence (p = 0.007) have a significant positive influence on revisit intention. Among these, people emerged as the most dominant factor, indicating that the quality of human resources covering attitudes, service delivery, friendliness, and the competence of healthcare staff is the key determinant of patients’ intention to return for treatment at dr. Agung Hospital.